Intentional Replantation: an Approach to Save Hopeless Natural Teeth (A Case Report) - soheila darmiani; Sediqe Ebrahimipour (Mashhad University of Medical Sciences, 2021)
Introduction: Non-surgical endodontic retreatment and surgical endodontic therapy may not be practical for the treatment of endodontic diseases. Intentional replantation is considered as a procedure of last resort when nonsurgical or surgical endodontics is contraindicated. Case report: A 35 year- old female attended the endodontist office with pain and apical lesion in endodontically treated tooth ≠47. Access preparation for retreatment is a problem due to the posts and crown and surgical endodontic therapy was limited by anatomical features including nerve proximity and bone thickness. In addition, the patient could not afford to pay for non-surgical re-treatment or implant therapy Conclusion: This report demonstrates intentional replantation as a treatment that can be considered when other options such as endodontic retreatment or apical surgery are impossible.